Qualitative assessment of temporal fluctuations on buffalo behaviour - Maria Serrapica; Ada Braghieri; Amelia Maria Riviezzi; Andrea Bragaglio; Angela Carlucci; Fabio Napolitano (Italian Journal of Agronomy, 2014)
The qualitative assessment of animal behaviour (QBA) is an integrative, whole-animal methodology based on the qualitative interpretation of the dynamic style in which animals interact with their environment. In other words, it describes not what the animals do, but how they do what they do. We aimed to verify whether the QBA was able to detect the behavioural fluctuations occurring in animals in response to an environmental challenge. An 8-member panel was used. The panel was briefly trained on the temporal dominance of sensations (TDS) procedure and subsequently asked to observe the behaviour of 4 buffalo heifers in 4 videos lasting 2 min each and score the behavioural expression of the animals following the TDS procedure. TDS consists in presenting to the panellist the list of behavioural descriptors on a computer screen along with each video. Each video was obtained by assembling two clips concerning the same animal in two different conditions: home indoor pen (1 min) and novel outdoor paddock (1 min). Two videos started with the animal in the outdoor environment and two others in the opposite order. Six behavioural descriptors were chosen from a previous work conducted on the same animals: calm, active, curious, nervous, shy and apathetic. Each assessor was asked to select the dominant descriptor, which was considered as dominant when it gained most of the attention of the observer. Each time the observer felt the behaviour changed, he/she scored the new dominant descriptor until the behaviour ended. Each video was observed 4 times by each observer (4 replications) in a randomised order at 24-h intervals. For each point of time, the proportion of runs (subject × replication) for which a given descriptor was assessed as dominant (dominance rate >30%) was computed. Results showed a satisfactory agreement among observers and replications. The observers clearly discriminated the first from the second half of each video. Calm and apathetic were dominant indoors, nervous and active were dominant outdoors, whereas curious was used in both conditions. In addition, the combination QBA-TDS showed how the behaviour changed in time (e.g. habituation to the novel environment) in outdoor conditions (the dominance of nervous and active at the start switched to calm at the end in 3 out of 4 videos), whereas indoors the animals showed reduced behavioural variations, possibly because they were habituated to those conditions, thus they did not change their way to interact with the environment.